Effect of Light Quality and Quantity on the Accumulation of Flavonoid in Plant Species - Idris, Aisha; Linatoc, Alona C; Abu Bakar, Mohd Fadzelly; Ibrahim, Zakiyyu Takai; Audu, Yunusa (Journal of Science and Technology, 2018)
Light effects including its intensity, wavelength, and duration are important environmental factors that affects flavonoid accumulation. Ultraviolet (UV) light can induce flavonoid biosynthesis. Under normal condition, flavonoids are produced in response to stress, and they function as UV filters. In this paper, we review how light quality and quantity affect the accumulation of flavonoid in plant species. High light intensity can influence flavonoid accumulation, but in heliophytes, the opposite is true. Some medicinal plants require shady environment for flavonoid accumulation. In monocots, the flavonoid is situated in both epidermis and mesophyll while in dicot, it is found only in the epidermis. This review leads to a conclusion that high variation in flavonoids accumulation in response to light can occur within and between plant species.